Development of a nomogram based on serum cytokine-related riskscore in breast cancer - Zhu, Ye; He, Yang; Chen, Chong; Zhang, Jingyi; Yang, Xin; Lu, Yuqing; Chen, Yong-Zi; Zhao, Weipeng (Frontiers in Oncology, 2023)
Background：Cytokines are involved in many inflammatory diseases and thus play an important role in tumor immune regulation. Recent years, researchers have found that breast cancer is not only related to genetic and environmental factors, but also to the chronic inflammation and immunity. However, the correlation between serum cytokines and blood tests indicators is remain unclear. Methods： A total of 84 serum samples and clinicopathological data of breast cancer patients from Tianjin Medical University Cancer Institute and Hospital were collected. The expression levels of 12 cytokines were detected by immunofluorescence method. Blood tests results were obtained from medical records. By stepwise Cox regression analysis, a cytokine-related gene signature was generated. Univariate and multivariate Cox regression were used to analyze the influence on the prognosis of patients. A nomogram was constructed to illustrate the cytokine-related riskscore predicting 5-year OS, which was further evaluated and validated by C-index and ROC curve. The correlation between the expression of cytokines in serum and other blood indicators was studied by using Spearman's test. Results： The riskscore was calculated as IL-4*0.99069 + TNF-α*0.03683. Patients were divided into high and low risk groups according to the median riskscore, with the high-risk group has a shorter survival time by log-rank test (training set, P=0.017; validation set, P=0.013). Combined with the clinical characteristics, the riskscore was found to be an independent factor for predicting the OS of breast cancer patients in both training cohort (HR=1.2, P<0.01) and validation cohort (HR=1.6, P=0.023). The 5-year C-index and AUC of the nomogram were 0.78 and 0.68, respectively. IL-4 was further found to be negatively correlated with ALB. Conclusion：In summary, we have developed a nomogram based on two cytokines including IL-4 and TNF-α to predict OS of breast cancer and investigated their correlation with blood test indicators.